2011
DOI: 10.1093/eurheartj/ehr130
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency is associated with adverse outcome in Eisenmenger patients

Abstract: Iron deficiency was associated with a higher risk of adverse outcome. Moreover, the use of oral anticoagulation OAC and frequent phlebotomies were related to iron deficiency. Patients under anticoagulation should be monitored rigorously for iron deficiency. However, in patients with low oxygen saturations, careful iron substitution to avoid too high haemoglobin levels is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 30 publications
0
49
0
4
Order By: Relevance
“…In all of these entities, preliminary data indicate that iron deficiency may be associated with reduced exercise capacity, and perhaps also with a higher mortality, independent of the presence or severity of anaemia [181,182,184,185]. Based on these data, regular monitoring of the iron status should be considered in patients with PAH and detection of an iron deficiency should trigger a search for potential reasons.…”
Section: Anaemia and Iron Statusmentioning
confidence: 99%
“…In all of these entities, preliminary data indicate that iron deficiency may be associated with reduced exercise capacity, and perhaps also with a higher mortality, independent of the presence or severity of anaemia [181,182,184,185]. Based on these data, regular monitoring of the iron status should be considered in patients with PAH and detection of an iron deficiency should trigger a search for potential reasons.…”
Section: Anaemia and Iron Statusmentioning
confidence: 99%
“…If moderate-to-severe symptoms of hyperviscosity are present, and iron deficiency and dehydration have been excluded, phlebotomy with isovolumic replacement should be performed carefully when the haematocrit is .65% [38]. Iron deficiency has been shown to be associated with a higher risk of adverse outcomes (allcause mortality, transplantation and hospitalisation due to cardiopulmonary causes) in Eisenmenger's syndrome patients [39] and iron replacement therapy improves exercise tolerance and QoL [40]. However, care should be taken in patients with low oxygen saturations to avoid haemoglobin levels becoming too high [39].…”
Section: General Management Of Pah-chdmentioning
confidence: 99%
“…Iron deficiency has been shown to be associated with a higher risk of adverse outcomes (allcause mortality, transplantation and hospitalisation due to cardiopulmonary causes) in Eisenmenger's syndrome patients [39] and iron replacement therapy improves exercise tolerance and QoL [40]. However, care should be taken in patients with low oxygen saturations to avoid haemoglobin levels becoming too high [39]. There are no data to support the use of calcium channel blockers in patients with PAH-CHD and their use must be avoided [3].…”
Section: General Management Of Pah-chdmentioning
confidence: 99%
“…A study of 68 patients by Van De Bruaene et al found that patients with resting oxygen saturations of <83% often reached Hb concentrations in the range that may be considered "at risk" for hyperviscosity symptoms when treated for iron deficiency and suggested closer monitoring for hyperviscosity symptoms in this group. 34 As iron deficiency is strongly related to adverse outcomes, particularly in those on anticoagulation or those having inappropriate venesection, it is important to regularly screen patients for this and treat when appropriate.…”
Section: General Management Of Eisenmenger Syndromementioning
confidence: 99%
“…OACs are associated with an increased risk of iron deficiency anemia and patients should be routinely investigated for this. 34 Also, endothelin receptor antagonists (ERAs) can reduce the efficacy of anticoagulants such as warfarin; therefore, necessitate close monitoring of the international normalized ratio is needed to maintain an adequate therapeutic index. Novel OACs have not been tested in this group and there are concerns regarding the limited availability of direct reversing agents.…”
Section: Oxygen Therapymentioning
confidence: 99%